Enacting friendship and negotiation online identities in facebook among a group of Malaysians - Lai, Yuh Ying (2014)
Facebook, one of the leading social-networking sites nowadays has become a necessary communication medium in our life. Facebook has tremendous influence to friendship and identity, thus this study attempts to investigate performing friendship and negotiating online identities by a group of Malaysian in Facebook. To determine the way friendship is performed in Facebook, this study investigated three aspects. Firstly, friendship behavior categories that are observed in posted messages. Secondly, social or communicative functions of the interaction mode in friendship behavior categories. In addition, to determine the way online identities are negotiated in Facebook, this study also investigate the types of online identities constructed and the way online identities are negotiated through message posted and comments in Facebook. Lastly, this study attempted to determine the relationship between online identities and friendship in Facebook. This study employed purposive sampling. Five Facebook users participated in this study. There are four theories selected to construct conceptual framework. These theories are Social Network Theory, Hyperpersonal Model, Self-presentation Theory and Social Identity Theory. Content analysis approach was used to analyse posted messages and comments. Interviews about relationship of participants and their friends, as well as reasons they posted messages online, were conducted to achieve the objectives of the study. It is concluded that Facebook is an additional medium to perform friendship. The social-networking site provides another channel for individuals to initiate and maintain friendship. With the resources provided on Facebook, a group of Facebook users manipulated the available resources to expand their network and presented themselves. Facebook resources especially the mode of interaction constrains the way friendship is performed and identities are negotiated in Facebook realm. Facebook users posted messages about themselves and started to connect with their friends with textual or visual information which they desired were shared on Facebook. In addition, Facebook is a form of social-networking site for individuals to project their identities online. Facebook has negotiated their online identity construction where individuals presented themselves as a thoughtful, sociable, well-roundedness, caring, authoritative, optimistic and expressive person. Participants and their respondents projected more than one identity to perform their friendship online. These can be seen when participants negotiated their identity as a friend to other identities such as motivator, broadcaster and computer expert. They negotiated different identities while communicating with different people in different communication contexts. This study makes several significant contributions. This study has contributed to the understanding of Facebook phenomenon in Asia region and the understanding of Facebook usage among adults. Suggestions for future studies on performing friendship and negotiating identities can be conducted on different regions and contexts, age range, number of subjects with different background and various types of online communication mediums. The comparative study of various categories mentioned above also worthwhile to be researched as well.